CLINICAL EFFICACY AND SAFETY OF AND A-2 ANTAGONIST EPROSARTAN IN PATIENTS WITH MILD AND MODERATE HYPERTENSION. RESULTS OF A MULTICENTER TRIAL - L. I. Olbinskaya; T. B. Andrushicina (Российский кардиологический журнал)
Clinical efficacy and safety of and A-2 antagonist eprosartan in patients with mild and moderate hypertension. Results of a multicenter trial.